Avoiding the Last Ride: Can DUI Programming Address Multiple Risk Factors to Reduce Recidivism?. Issue 2 (3rd October 2018) - Gibson, Sandy; Woodford, Mark; Czeizinger, Thomas J.
Abstract : A review of DUI education literature reveals weak evidence of effective interventions. New models are suggested that offer a combination of psychoeducation and evidence‐based counseling approaches. Existing DUI programming models are explored with recommendations for areas for future research.